TINJAUAN HUKUM DAN IMPLEMENTASI HUBUNGAN PEMERINTAHAN DESA DENGAN BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA : Studi Kasus di Desa Kedung Waringin Timur Kabupaten Bogor - Cucuk Endratno (Universitas Nasional, 2020)
This study examines the Legal Review of the Relationship between the Village Government and the Village Consultative Body in Village Development (Case Study in the Kedung Waringin Timur Village, Bogor Regency). The village as a government that directly touches the community is the main focus in government development, this is because most of Indonesia's territory is in the countryside.The problem of this research is how the relationship between the Village Government and the Village Consultative Body in development in the Village of Kedung Waringin, Bogor Regency and what factors are hampering the Village Government and the Village Consultative Body in carrying out development in the Kedung Waringin village, Bogor Regency. Based on Law No. 6 of 2014 concerning villages, each village is expected to be able to increase Human Resources for village development. The research method used is a normative jurisdiction of qualitative analysis. Sources of data obtained are primary data and secondary and tertiary data.The results showed that the pattern of cooperative relations between the Village Consultative Body and the village government had been established by the Regional Regulation of the South Minahasa District Number 3 of 2016 on the Village, where the pattern of the working relationship between the BPD and the Village Head was a pattern of partnership relations in carrying out the tasks of village government. The creation of a working relationship between the Village Consultative Body and the Village Government in the village of Kedung Waringin is very important and is able to create a working partner relationship, not the opposition especially the collusion partners between the Village Head and the Village Consultative Body. The Village Consultative Body is a people's representative whose main function is to control the implementation of the Village Government given the importance of the Functions of the Village Consultative Body, it must be supported by efforts to constantly remind the quality of its members so that they are able to carry out their functions in the oversight of the administration to the maximum.